O papel do servicescape em lojas de parques e resorts temáticos: um estudo de caso a partir da perspectiva dos funcionários - Cezar, Maria Eduarda Canaparo Zago (Universidade Federal de São Carlos, 2025)
This study analyzes how servicescape elements manifest in retail stores located within theme parks and resorts and how they contribute to the consumer experience, from the employees’ perspective. The research adopts a qualitative and descriptive approach, based on an experience report conducted in a real themed retail environment, complemented by interviews with five employees who worked in stores within the same context. The results indicate that elements such as layout, product organization, atmosphere, support technologies, and customer service play a fundamental role in shaping the experience, promoting journey fluidity, thematic immersion, and interactions with visitors. It is concluded that the servicescape operates in an integrated manner as a central element in creating engaging experiences and generating perceived value in themed retail.
The role of the servicescape in theme park and resort retail stores: a case study from employees’ perspectives
Keywords: Servicescape; Parque temático; Varejo tematizado; Consumo simbólico; Theme park; Consumer experience; Themed retail; Symbolic consumption.; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO; 8. Trabalho Decente e Crescimento Econômico